2018
DOI: 10.1007/s00784-018-2500-4
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetic efficacy of mental/incisive nerve block compared to inferior alveolar nerve block using 4% articaine in mandibular premolars with symptomatic irreversible pulpitis: a randomized clinical trial

Abstract: MINB and IANB with 4% articaine can be used interchangeably to anesthetize mandibular premolars with irreversible pulpitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Thirteen trials were the result of international cooperation between two countries, mostly United States and Iran ( n = 4), whilst only one trial reflected cooperation between the authors of three different countries, namely the United States, UK and Iran (Ghabraei et al . 2019). The relationship amongst the most prolific countries, authors and journals in which clinical trials were published are illustrated in a Sankey plot (Figure 4; Interactive version – Figure S2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirteen trials were the result of international cooperation between two countries, mostly United States and Iran ( n = 4), whilst only one trial reflected cooperation between the authors of three different countries, namely the United States, UK and Iran (Ghabraei et al . 2019). The relationship amongst the most prolific countries, authors and journals in which clinical trials were published are illustrated in a Sankey plot (Figure 4; Interactive version – Figure S2).…”
Section: Resultsmentioning
confidence: 99%
“…2018, Ghabraei et al . 2019) had two corresponding authors from different continents and were excluded from the analysis. Journal (Endodontic specialty vs. Non‐Endodontic specialty journals): No significant difference was observed between the Endodontic specialty and Non‐Endodontic specialty journals in terms of the quality of the reporting of clinical trials. Non‐Endodontic speciality journals (62%) were associated with the greatest percentage of ‘High’‐quality clinical reports compared to Endodontic speciality journals (38%).…”
Section: Resultsmentioning
confidence: 99%
“…The onset of anaesthesia was faster and pain on injection was significantly less when the MINB was used. However, post‐injection pain was higher compared with the IANB (Ghabraei et al, 2019). It has been reported that for anesthetizing mandibular incisor teeth with irreversible pulpitis, bilateral MINB with 2% lidocaine with 1:80 000 epinephrine significantly improved the success rate of anaesthesia compared to a unilateral MINB injection (Kumar et al, 2020).…”
Section: Anaesthetic Techniquesmentioning
confidence: 99%
“…Therefore, another technique with adequate anesthetic efficiency and low complexity is needed. Despite some studies have evaluated similar techniques (buccal infiltration) as an alternative to IANB in anesthetizing the mandibular posterior teeth [ 33 , 43 50 ], most of them either used 4% articaine alone [ 33 , 43 , 44 , 47 , 50 ], or preferred it over lidocaine as the anesthetic agent [ 46 , 48 , 49 ]. In dentistry, 4% articaine has been used as a local anesthetic agent for many years and it was reported to be better in ensuring pulpal anesthesia than a 2% lidocaine solution.…”
Section: Discussionmentioning
confidence: 99%